Greater temperature sensitivity of plant phenology at colder sites: implications for convergence across northern latitudes. (6th February 2017) - Prevéy, Janet; Vellend, Mark; Rüger, Nadja; Hollister, Robert D.; Bjorkman, Anne D.; Myers‐Smith, Isla H.; Elmendorf, Sarah C.; Clark, Karin; Cooper, Elisabeth J.; Elberling, Bo; Fosaa, Anna M.; Henry, Gregory H. R.; et al.
Abstract: Warmer temperatures are accelerating the phenology of organisms around the world. Temperature sensitivity of phenology might be greater in colder, higher latitude sites than in warmer regions, in part because small changes in temperature constitute greater relative changes in thermal balance at colder sites. To test this hypothesis, we examined up to 20 years of phenology data for 47 tundra plant species at 18 high‐latitude sites along a climatic gradient. Across all species, the timing of leaf emergence and flowering was more sensitive to a given increase in summer temperature at colder than warmer high‐latitude locations. A similar pattern was seen over time for the flowering phenology of a widespread species, Cassiope tetragona . These are among the first results highlighting differential phenological responses of plants across a climatic gradient and suggest the possibility of convergence in flowering times and therefore an increase in gene flow across latitudes as the climate warms. Abstract : Warmer temperatures are accelerating the phenology of organisms around the world, and temperature sensitivity of phenology might be greater in colder, higher latitude sites than in warmer regions. We tested this hypothesis using phenology data for 47 tundra plant species at 18 high‐latitude sites along a climatic gradient. Across all species, the timing of leaf emergence and flowering was more sensitive to a given increase in summer temperature at colder than warmer high‐latitude locations. These are among the first results highlighting differential phenological responses of plants across a climatic gradient and suggest the possibility of convergence in flowering times and therefore an increase in gene flow across latitudes as the climate warms. (Photo credit: Anne D. Bjorkman)